2009
DOI: 10.1109/mis.2009.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Thesaurus Alignments for Semantic Interoperability in the Library Domain

Abstract: Published by the IEEE Computer Societyother controlled vocabularies) specific to fields, institutions, and even collections. The desire to make CH resources available to the general public (for example, see www. europeana.eu) increases the need to facilitate interoperability across different contexts.By providing representational standards such as the Simple Knowledge Organization System (SKOS; www.w3.org/2004/02/skos) and generic tool support, the Semantic Web community has taken a prominent role in this faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…It involves the use of a technological platform that includes a thesaurus [18] and a set of ontologies, implemented using Protégé [19]. The difference between a thesaurus and an ontology is that the thesaurus does not contain any axioms that allow any kind of automatic reasoning to be performed.…”
Section: Semantic Alignmentmentioning
confidence: 99%
“…It involves the use of a technological platform that includes a thesaurus [18] and a set of ontologies, implemented using Protégé [19]. The difference between a thesaurus and an ontology is that the thesaurus does not contain any axioms that allow any kind of automatic reasoning to be performed.…”
Section: Semantic Alignmentmentioning
confidence: 99%
“…While the design of our repository services takes into account general needs of vocabulary experts, its current implementation responds to direct requirements of the STITCH project and its umbrella programme CATCH [4].…”
Section: Use Cases Requirements and Backgroundmentioning
confidence: 99%
“…theeuropeanlibrary.org/telplus/) investigated methods to support metadata interoperability by automatically identifying inter-vocabulary semantic mappings [1,2]. They showed that the automatic matching of vocabularies can be the basis of various real-world usage scenarios, including support for indexing and re-indexing collection items, inter-collection search and navigation, but also thesaurus management [3,4]. First tools for vocabulary services have been deployed at the National Library of the Netherlands, so that there is indeed an industrial uptake of Semantic Web technology in this context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these books (nearly 238K) are thus indexed with both Biblion and Brinkman. Following the reindexing evaluation approach of [11], we used the existing Brinkman subjects of these books as a gold standard with which we could automatically compare new suggested subjects. Based on the low performance of this preliminary automatic evaluation, we decided to drop these first suggestion rules.…”
Section: Brinkman Subject Suggestion Rulesmentioning
confidence: 99%